Anti-conflictualist and liberal minimalism of rights: an analysis from the perspective of interest theory and the dynamic approach - Zezza, Michele (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
The article describes two different minimalist approaches in the field of recognition and protection of rights: the anti-conflictual and the liberal variants. It explores their historical-cultural assumptions and highlights their main elements of their unreasonableness. To this end, we use some theoretical tools deriving from the combination of interest theory with a dynamic approach.